From Laṅkā Eastwards; The Rāmāyaṇa in the Literature - Acri, Andrea (Verhandelingen van het Koninklĳk Instituut voor Taal-, Land- en Volkenkunde, 2011)
The Kakawin Ramayana, arguably the oldest Old Javanese epic text in Indic metres (circa 9th century AD), holds a unique position in the literary heritage of Indonesia. The poem has retained a remarkable vitality through the centuries in the Archipelago, inspiring many forms of artistic expression not only in the domain of literature but also in the visual and performing arts, from the reliefs of the majestic Central Javanese temples to modern puppet-show performances. Displaying a virtuoso array of metrical patterns, the Kakawin Ramayana is among the very few Old Javanese texts for which a specific Sanskrit prototype has been identified, namely the difficult poem Bhattikavya (circa 7th century AD), itself a version of the great Ramayana epic ascribed to Valmiki (circa 6th-1st century BC). The Old Javanese poem is an original and skillful work of re-elaboration that documents a fascinating interaction between cultural elements of the Sanskritic tradition with those indigenous to the Javanese setting. The studies included in this volume, written by experts in a wide range of disciplines, focus on disparate aspects of the Kakawin Ramayana and the constellation of cultural phenomena revolving around it, providing the reader with a key to the understanding of the rich Old Javanese textual heritage and the transcultural intellectual dynamics that contributed to shaping the cultural heritage of Indonesia up to the present. With contributions from Andrea Acri, Helen Creese, Arlo Griffiths, Thomas Hunter, Roy Jordaan, Lydia Kieven, Cecelia Levin, Wesley Michel, Stuart Robson and Adrian Vickers, this book is the result of a workshop held at the KITLV branch in Jakarta on May 26th-28th 2009 and supported by the Australia-Netherlands Research Collaboration, the École française d'Extrême-Orient, and the Stichting J. Gonda Fonds.